Black Magic and Bogeymen : Fear, Rumour and Popular Belief in Northern Ireland 1972-74 - Jenkins, Richard, 1952- (Book collections on Project MUSE., 2014)
This is an analysis of a popular scare about black magic and Satanism in Northern Ireland in Northern Ireland between 1973 and 1974. The book gives an insight into a particularly grim period during the early 1970s in Northern Ireland, using an extremely unusual episode - the black magic rumours - as a privileged window onto a world that may now be behind us, but which continues to fascinate many readers. The book provides a fascinating insight into some of the problems and procedures of social history. The author demonstrates that phenomena like the black magic rumours cannot be understood without taking a multidisciplinary approach, taking in perspectives and comparative evidence from anthropology, sociology, folklore and media studies.